2020
DOI: 10.3390/membranes10120391
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Porosity and Permeability of a Polymer Filter Fabricated via CO2-Assisted Polymer Compression

Abstract: A porous filter was fabricated by plasticizing polymer fibers with CO2, followed by pressing and adhering; then, its gas permeability, a basic physical property of filters, was measured using N2. The as-obtained filter was well compressed and expected to approximate a sintered porous material. Therefore, the fabricated filter was analyzed by applying the Darcy law, and the correlation between its gas permeability and porosity was clarified. The gas permeability decreased owing to both pore size and porosity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In the last years, the study of different multiform geometry by continuous mathematics and numerical approximation has been increased in the computer graphics area [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In this work, an algorithm is developed to analyze the geometric behavior of polygonal synthetic agglomerate (PSA) from circles and polygons of 3–5 sides.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, the study of different multiform geometry by continuous mathematics and numerical approximation has been increased in the computer graphics area [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In this work, an algorithm is developed to analyze the geometric behavior of polygonal synthetic agglomerate (PSA) from circles and polygons of 3–5 sides.…”
Section: Methodsmentioning
confidence: 99%
“…Among the applications using synthetic images are the development of renewable energy such as synthesis of materials and prediction of behaviors for fuel cells [ 9 ], devices and apps for medicine (magnetic resonance imaging) [ 11 ], neural networks mainly with the use of Deep Learning [ 12 ], materials for ultra-fast devices in the telecommunications area (ultra-fast devices) [ 13 , 14 ], military applications such as radars and ship detection simulators [ 15 ], and topographical images of polymer solar cells [ 16 ]. There are other works involved in the improvement of microstructures related to comparison of different morphologies on 3D reconstructions [ 17 ], the behavior of their geometry to conversion of triangular to hexagonal models [ 18 ], synthesis of palladium nanoparticles in triangular form [ 19 ], Finite Volume Method (FVM) for morphology studies of microstructures with mechanoluminescent particles [ 20 ], heat and humidity transfer in clothing sets, using the finite volume method for the nonlinear parabolic equations system [ 21 ], computational thermal conductivity and membrane pore geometry simulation in porous materials [ 22 , 23 ], tortuosity, permeability and threshold percolation studies from membrane SEM images and transport pore structure [ 24 , 25 , 26 ], images generation from mathematical descriptors for 3D shapes analysis using formal segmentation [ 27 ], structural detail analysis of woven fabric based on synthetic images [ 28 ], thermal expansion coefficients calculation for one and two phases from SEM models and three-dimensional synthetic images of polycrystals [ 29 ], geometric and topological characterizations to establish a relationship of the structure owned by two phases using the Voronoi diagram in geometry of synthetic images [ 30 , 31 ], neutron imaging in fuel cells research [ 32 ], and a systematic classification implemented by its geometric and topological properties focus on imitating morphology through mathematical tools, such as digital image correlation, tessellation, random field generation, and differential equation solvers [ 33 ]. Finally, synthetic anisotropic training is performed to reconstruct anisotropic media [ 34 ] and multiscale model-based on synthetic structures, using isotropic filtering [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this sample has greatest thickness (0.16 mm) than the other samples, yet it also has the largest pore size (3715 ± 10 nm) which rationalizes the highest air permeability. Aizawa and Wakui reported that gas permeability is a function of nanofibers porosity in a direct relationship (Aizawa & Wakui, 2020).…”
Section: Nanofiber Morphology and Propertiesmentioning
confidence: 99%
“…In addition, I have developed a simultaneous mass production technique (Aizawa, 2019b) and another production technique for producing multilayered membranes with di erent porosities by performing CAPC treatment in two steps (Aizawa, 2020). An analysis has also been presented of the pressure loss when used as a lter (Aizawa and Wakui, 2020). e main advantage of the CAPC method is that the same raw material can be used to fabricate various porous materials under di erent process conditions.…”
Section: Introductionmentioning
confidence: 99%